Voluntary Disclosure in Light of Control Concerns* - Arya, Anil; Ramanan, Ram N.V. (Contemporary Accounting Research, 2021)
ABSTRACT The centrality of private information in the design of accounting institutions has been explored via agency models that address control concerns as well as disclosure models that amplify valuation issues. This paper derives disclosures by an entrepreneur‐owner when both control and valuation concerns are in play. In particular, the disclosures influence stock price not only via a direct impact on valuation of the firm's revenue but also via an indirect impact on the firm's cost of procuring inputs from a self‐interested and privately informed upstream supplier. In this setting, disclosures are judiciously designed to influence the supplier's decision to share cost information and to control information rents embedded in the procurement contract within the supply chain. Specifically, in order to convey that information rents are not in the offing and, thus, motivate information sharing by the supplier, the owner has incentives to convey a less “rosy” picture. In effect, when controlling supplier actions also becomes important, the owner discloses some unfavorable revenue news that she would have otherwise withheld and conceals some favorable revenue news that she would have otherwise revealed. Consequently, in our model, the disclosure region is either two‐tailed or intermediate, in contrast to the single‐tailed disclosure region implied by familiar valuation considerations alone.